(untitled) (Annals of Medical Research, 2021)
Aim: The purpose of our study was to compare the McGrath MAC videolaryngoscope (VL) with the Macintosh direct laryngoscope (DL) for the efficacy during nasotracheal intubation (NTI) in patients undergoing dental surgery. Material and Methods: In total, 70 American Society of Anesthesiologist physical status (ASA) I-II patients who underwent elective dental surgery requiring NTI were included in this study. The patients were divided to two groups based on intubation using McGrath MAC VL (n=35) and Macintosh DL (n=35). The patients were monitored via electrocardiography (ECG), noninvasive arterial pressure, and peripheral oxygen saturation (SpO2) after they were taken to the operating room. Preoxygenation was performed with face mask for at least 3 minutes with 100 % O2. In addition, 2 mg/kg propofol and 1 µg/kg fentanyl were administered for anesthesia induction, and 0,6 mg/kg rocuronium was administered for muscular relaxation. NTI was performed 3 minutes after rocuronium injection with a nasotracheal tube. Anesthesia was maintained with sevoflurane and 50% air in oxygen. Mean arterial pressure (MAP), heart rate (HR), SpO2 and end tidal-carbon dioxide (EtCO2) were recorded at baseline; after anesthesia induction; and 1st, 2nd, 3th and 5th minutes after intubation. Cormack-Lehane and Mallampati Scores (MPS), laryngeal compression, duration of intubation, using Magill forceps, ease of intubation, and the incidence of complications due to intubation were recorded. Results: The demographic characteristics of the groups were similar. Regarding the success of the intubation, no significant difference was detected between the McGrath MAC VL group and the Macintosh DL group (p >0,05). However, when intubation times were compared, a significant difference was noted between groups (p<0,05). The intubation time was reduced in the McGrath MAC VL group. No statistically significant difference was observed regarding MAP and HR values. Intubation using McGrath MAC VL was significantly easier than direct laryngoscopy (p<0,05). No difference in complications was observed (p>0,05). Conclusion: We compared the McGrath MAC VL with the Macintosh DL for NTI and found that intubation was applied in less time using McGrath MAC VL than Macintosh DL. Intubation was more easy with McGrath MAC VL than Macintosh DL. We believe that McGrath MAC VL can be preferred to DL for NTI.